2005
DOI: 10.1128/cdli.12.10.1202-1208.2005
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Feline Dendritic Cells Derived from Peripheral Blood Monocytes for In Vivo Use

Abstract: Dendritic cells (DCs) are professional antigen-presenting cells that can prime T cells and polarize the cellular immune response. Because Th1-type immune responses have been connected to success in combating viral infection, a promising therapeutic application of DCs would be their differentiation in vitro and injection back into the host to boost an immune response in infected animals. This study was aimed both at developing a protocol to cultivate feline DCs in the absence of exogenous proteins for their use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…We have previously described the generation of feline MDCs in conditions established to avoid any contact of the cells with foreign protein, implying the use of autologous plasma and feline cytokines. We have also shown that the only maturation stimulus tested leading to full feline MDC maturation in the cat was LPS and that the most suitable surface markers to follow maturation were MHC-II and B7.1 expression levels, while the best functional assay was considered to be MLR (2,3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously described the generation of feline MDCs in conditions established to avoid any contact of the cells with foreign protein, implying the use of autologous plasma and feline cytokines. We have also shown that the only maturation stimulus tested leading to full feline MDC maturation in the cat was LPS and that the most suitable surface markers to follow maturation were MHC-II and B7.1 expression levels, while the best functional assay was considered to be MLR (2,3).…”
Section: Resultsmentioning
confidence: 99%
“…We then used the same virus isolate to challenge vaccinated cats. Although the feline DC maturation stage is not as straightforward to define as that for human DCs, where well-defined markers allow us to distinguish between mature and immature cells, correlates of feline MDC maturation, such as MHC-II and B7.1 expression levels and the ability to induce MLR, have been described previously (3). In the present study, after MDCs were loaded with antigen, the maturation stimulus used in vitro was LPS for all MDCs, because previous work has shown LPS is the only stimulus known to induce the ability of MDCs to start MLR in the feline model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All cats were shown to be positive for FIV antibody and negative for feline leukemia virus Cell preparation: The methods for the preparation of DCs and macrophages were modified based on previously described protocols [4,13,27]. Briefly, heparinized whole blood was layered onto Ficoll/Hypaque (Lymphoprep; Nycomed Pharma AS, Oslo, Norway) and centrifuged at 560 g for 45 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Monocytes incubated with granulocyte macrophage colony-stimulating factor (GM-CSF) and interleukin 4 (IL-4) acquire the properties of DCs. Moreover, several studies have been performed to establish a method for generating feline DCs [4,13,27]. Similar to human and murine DCs, feline DCs have been generated from monocytes cultured with GM-CSF and IL-4, and they also possessed the characteristic properties of DCs.…”
mentioning
confidence: 99%